MAQASHID AL-SYARIAH SEBAGAI KONSEP DASAR DALAM TEORI PEMBENTUKAN HUKUM ISLAM DI INDONESIA - Fathony, Alvan (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2018)
The majority of fuqoha 'has defined fiqh as a result of understanding, tashawwur and critical reasoning (al-idrak) of a mujtahid. But on the other hand, fiqh as a result of ijtihad teryata is often described as divine law (sharia). As Ijma '(consensus), there are many differences in defining it, but until now there are still many fuqoha' who regard ijma 'as qath'i propositions which are level with texts and are sariari-made propositions' and even claim that those who oppose ijma 'including infidels. Humans often traditionalize actions that are considered good and are their daily needs, so that Islam also still recognizes and contributes to maintaining the tradition (‘Urf) into a method of observation, not only maintaining it but because it pays more attention to the benefit of the people. Because Islam comes in the context of regulating the social order that is oriented towards achieving benefit and avoiding loss (madlarat), moreover the texts of the Shari'a itself do not provide a detailed solution to the diversity of problems of each community. Traditionally the implications of Urf are very limited to only space and time, while legal decisions continue to apply even in different situations and conditions. So the view of jurisprudence towards the world (jurist's worldview) is intended as the development of the Urf concept in order to achieve the universality of maqashid al-sharia.